2007
DOI: 10.1017/s0033291707000542
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based cognitive behavioural therapy for subthreshold depression in people over 50 years old: a randomized controlled clinical trial

Abstract: Background. Subthreshold depression is a highly prevalent condition and a risk factor for developing a major depressive episode. Internet-based cognitive behaviour therapy may be a promising approach for the treatment of subthreshold depression. The current study had two aims :(1) to determine whether an internet-based cognitive behaviour therapy intervention and a group cognitive behaviour therapy intervention are more effective than a waiting-list control group ; and (2) to determine whether the effect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
225
10
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 276 publications
(261 citation statements)
references
References 38 publications
16
225
10
7
Order By: Relevance
“…In one study, Internet-based CBT has been found to be effective in the treatment of subthreshold depression in older adults [ 9 ]. This study showed that Internet-based CBT had large effects on depressive symptomatology in older adults, and was as effective as a preventive group intervention.…”
Section: Internet-based Cbt As Preventive Intervention In Older Adultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In one study, Internet-based CBT has been found to be effective in the treatment of subthreshold depression in older adults [ 9 ]. This study showed that Internet-based CBT had large effects on depressive symptomatology in older adults, and was as effective as a preventive group intervention.…”
Section: Internet-based Cbt As Preventive Intervention In Older Adultsmentioning
confidence: 84%
“…The group format is often used, but in recent years, the Internet is used more and more in psychoeducational interventions, including the CWD for older adults [ 9 ]. The psychoeducational approach implies that the therapist works more in the role of an instructor or coach instead of a therapist, and the patient is more a student than a traditional patient.…”
Section: The "Coping With Depression" Course As Indicated Prevention mentioning
confidence: 99%
“…Only in a few studies a maximum age of 75 or 80 years has been used (f.i. Proudfoot et al, 2004;Spek et al, 2007). Knowing that at least part of the current people aged 75 years or older can already be reached via the Internet for teaching psychological techniques is important for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Other interventions too deviated from the standard CBT content, for example, problem-solving therapy (PST; van Straten, Cuijpers, & Smits, 2008), a structured writing intervention (SWI; Kraaij et al, 2010), a combination of face-to-face (F:F) and cognitive therapy (Wright et al, 2005), or mindfulness activities with standard CBT elements delivered in group format online (Thompson et al, 2010). Andersson et al (2005) included modules on behavioral activation, cognitive restructuring, sleep and physical health, and relapse prevention, a version of the program was also employed by .…”
Section: Computer-based Psychological Treatments For Depressionmentioning
confidence: 99%
“…Some of the studies included an examination of the lasting effects of the intervention, and included varying lenghts of follow-up assessments from 1 to 4 months (Thompson et al, 2010;Titov et al, 2010;Whitfield et al, 2006), 6 to 8 months Clarke et al, 2002Clarke et al, , 2005Grime, 2004;Holländare et al, 2011;Meyer et al, 2009;Wright et al, 2005), or 1 year and beyond Mackinnon, Griffiths, & Christensen, 2008;Spek et al, 2008;Topolovec-Vranic et al, 2010).…”
mentioning
confidence: 99%